Cephalometric variables used to predict the success of interceptive treatment with rapid maxillary expansion and face mask. A longitudinal study - Daniele Nóbrega Nardoni; Danilo Furquim Siqueira; Mauricio de Almeida Cardoso; Leopoldino Capelozza Filho (Dental Press Editora, 2015)
INTRODUCTION: Prognosis is the main limitation of interceptive treatment of Class III malocclusions. The interceptive procedures of rapid maxillary expansion (RME) and face mask therapy performed in early mixed dentition are capable of achieving immediate overcorrection and maintenance of facial and occlusal morphology for a few years. Individuals presenting minimal acceptable faces at growth completion are potential candidates for compensatory orthodontic treatment, while those with facial involvement should be submitted to orthodontic decompensation for orthognathic surgery. OBJECTIVES: To investigate cephalometric variables that might predict the outcomes of orthopedic treatment with RME and face mask therapy (FM). METHODS: Cephalometric analysis of 26 Class III patients (mean age of 8 years and 4 months) was performed at treatment onset and after a mean period of 6 years and 10 months at pubertal growth completion, including a subjective facial analysis. Patients was divided into two groups: success group (21 individuals) and failure group (5 individuals). Discriminant analysis was applied to the cephalometric values at treatment onset. Two predictor variables were found by stepwise procedure. RESULTS: Orthopedic treatment of Class III malocclusion may have unfavorable prognosis at growth completion whenever initial cephalometric analysis reveals increased lower anterior facial height (LAFH) combined with reduced angle between the condylar axis and the mandibular plane (CondAx.MP). CONCLUSION: The results of treatment with RME and face mask therapy at growth completion in Class III patients could be predicted with a probability of 88.5%.